A Comparison of Impact of Agri-tourism as Perceived by Multiple Stakeholders in Maharashtra and Goa - Krishna, D.K.; Kumbhare, N.V.; Sharma, J.P.; Rao, D.U.M.; Sharma, D.K.; Kumar, Pramod; Bhowmik, Arpan (Indian Journal of Extension Education, 2021)
The study was conducted to assess the impact of agro tourism as perceived by its stakeholders. Forty-five agri-tourism Centres (ATCs) drawn from Maharashtra (30) and Goa (15) and 200 visitors (100 from each state) were selected for the study. The impact was measured in terms of change in employment days and perceived overall socio-economic changes. An average number of employment days in Maharashtra and Goa had increased from 149 to 202 man-days/year and 117 to 208 man-days/year, respectively after 2016. Significant changes were observed in the installation of new irrigation system and new farm structure for activities and games in Maharashtra whereas in Goa, ATC farms witnessed significant improvement in the installation of new processing and post-harvesting equipment and arrangements for entertainment along with the installation of a new irrigation system. ATC hosts showed significant social changes in social participation, increase in external contacts, recognition and awards. A significant difference was observed among the compared benefits as perceived by tourists in terms of learning more about nature, to think about their values, recalling good times from the past and to have a change from their daily routine.
Keywords: Agri-tourism; Hosts; Employment; Socio-economic changes; Visitors